If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + 9x = -2 Combine like terms: -8x + 9x = 1x 1x = -2 Solving 1x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '1'. x = -2 Simplifying x = -2
| 5n+1=2n+3 | | 6.7x-3.4=16.7 | | 5x-9+4x=3x+30 | | 7p-23=-17+8p | | 2v+7=5v+4 | | 45=360+x | | 2r-16=-6+4r | | 4g+20=10g+5 | | Y=8sec(5x) | | 2(x-7)-9=-23 | | 5(3x+2)=7 | | 3n+2=1n+12 | | (x+10)(x+5)+(x+-3)(x+12)+(x+11)(x+30)=106 | | 2x^4=35 | | 1n+9=4n+3 | | -16x^2+240x+20=0 | | 2.5x+2.4=7.8 | | 4m-8+2m=2(3m-4) | | 3x^2-3=2x-1 | | 3n+6=4n+1 | | 5-21=2a | | solvex+0.08(60)=0.20(60+x) | | 3(x+5)=x+3+2x | | Sen(2x)+sen(4x)=0 | | 47.1=29.7-0.2x | | -47(x-11)-34=10-12 | | 2m-28=9m | | 2-7k=-4(k+1)-3 | | 4(x-8)=2x+6-x | | 3z-19=123 | | 2[t-(2t+8)+6]=2(t+2) | | 5x(x+8)+5x(6-x)=9(12+x)-8(7-x) |